ION IMPRINTED POLY(PHENOL-FORMALDEHYDE) WITH MAGNETITE CORE FOR CADMIUM PRECONCENTRATION AND ANALYSIS - PRATIWI (NIM : 10512079), RISMA
In this research, Poly(Phenol-Formaldehyde)-Cd(II) with magnetite core (Cd-IPPF@Fe3O4) has been successfully synthesized for cadmium preconcentration and analysis. Cadmium is one of heavy metals that have toxic effect for health and usually measured by Atomic Absorption Spectrometry (AAS). However, the sensitivity and limit of detection for this method is low in trace level concentration with complex sample matrices. In order to solve this problem, preconcentration by SPE is done. IIP was prepared by copolymerization of phenol and formaldehyde with Cd-acetate and magnetite under alkaline conditions. The trapped Cd(II) was completely removed by leaching the dried and powdered imprinted polymer with 1 M HNO3 to obtain Cd(II) template. This polymer has been characterized by FTIR, SEM, and EDS. Retention characterization is done by batch method. Characterization using batch method showed that the optimal condition of Cd-IPPF@Fe3O4 towards Cd(II) was at pH 4, 39 minutes of contact time with recovery percentage 101.52%. Adsorption capacity of NIPPF@Fe3O4 and Cd-IPPF@Fe3O4 are 12.23 mg/g and 21.01 mg/g. Analysis and preconcentration of river water sample using Cd-IPPF@Fe3O4 shown the concentration of cadmium was 10.66 ppb with recovery percentage 108.5%.